Unilateral Bartholin Gland Cyst In A Cow And Its Surgical Management - A Case Report - Anil Kumar Sharma,; Rashmi Thakur, (The Indian Veterinary Journal, 2023)
The major vestibular or bartholin glands secrete mucous most actively during estrus and have a tubule-alveolar structure. A seven months pregnant Jersey Cross bred heifer aged around 2.5 years was presented with a round mass coming out of vagina. On per vaginal examination it showed unilateral bartholin gland cyst. The cyst was first drained using 18 gauge needle puncture.  After that its margins were excised and then re-structuring of tissue was done using vicryl suture 0.